The relationship is everything : women’s reasons for, and experience of maternity care with a privately practising midwife in Western Australia - Davison, Clare Louise (Curtin University, 2014)
The aim of this descriptive qualitative study was to investigate women’s reasons for, and experiences of maternity care with a privately practising midwife. Data analysis from the fourteen women interviewed revealed three major categories characterising reasons for choosing private midwifery care: I knew what I wanted from my care provider; I knew what I wanted from my pregnancy and birth experience and I was willing to do the research to get what I wanted.